Ultrasonographic scan in knee pain in athletes. Issue 2 (June 1992) - Maffulli, N; Regine, R; Carrillo, F; Minelli, S; Beaconsfield, T
Abstract : Fifty-two knees were examined using real-time high-definition ultrasonography with a 7.5 MHz probe. The extra-articular structures were easily visualized and diagnosis of patellar tendon lesions and Baker's cysts formulated. While the meniscal cartilages were shown as a homogeneous triangular structure between the femoral condyle and the tibial plateau, no lesions were detected. Deeper intra-articular structures, such as the cruciate ligaments, were not shown by the scan, thus their evaluation was not possible. Given its low cost, wide availability, non-invasiveness and patients' acceptability of the technique, ultrasonography may play an important role in the diagnosis of soft tissue lesions in and around the knee joint.